KORELASI KADAR ASAM URAT DALAM DARAH TERHADAP LUARAN KLINIS STROKE ISKEMIK AKUT - Daniel Mahendrakrisna; Aria Chandra Gunawan Triwibowo Soedomo (PERDOSNI, 2020)
Background: Uric acid is an end metabolism product of purine. It has been known as an important antioxidant in the serum. Correlation between uric acid serum with stroke has been reported controversial finding. However, Uric acid has been proposed to be a stroke risk factor. Aim: To determine the correlation between uric acid serum levels and acute stroke ischemic outcome. Method: This was a cross-sectional study at Surakarta Hospital. All of first experience stroke ischemic patients proven by CT-Scan were included as subjects. Demographic data (age, sex, blood pressure, etc) and laboratory results such as uric acid 24 hours, blood glucose test (random glucose test and fasting glucose test), lipid profile (cholesterol, triglyceride) were obtained from medical records. Data was analysed by software and p<0.05 was statistically accepted. Results: Of 49 acute stroke ischemic patients were include to this study. The mean of uric acid level serum as 5.71±2.64 mg/dL. 30,6% subjects had hyperuricemia and 8,2% subjects had hypouricemia. There were no correlation between uric acids levels with stroke clinical outcome (r= 0.08, p>0.05). Conclusion: There was no correlation between uric acid serum levels and acute stroke ischemic outcome.. Keywords: Ischemic, Modified Rankin Scale,